Maternal stress during pregnancy increases neonatal allergy susceptibility: Role of glucocorticoids - Lim, Robert (American Physiological Society, 2014)
We sought to test experimentally whether maternal stress can promote susceptibility to development of asthma-like allergic airways disease in offspring. Normal pregnant mice (day 15) were subjected to a single restraint stress exposure. We subsequently tested their offspring for the development of airway hyperreactivity (AHR) and allergic airway inflammation (AI), after an intentionally suboptimal sensitization protocol. The offspring of stressed mothers showed levels of AI and enhanced airway responses to methacholine comparable to those seen in fully sensitized and challenged positive control animals; in contrast, minimal effects were seen in control offspring. Restraint stress caused a rapid and large increase in plasma corticosterone levels. Maternal treatment with dexamethasone on day 15 of pregnancy mimicked the stress effect and reproduced the AI and AHR outcomes, whereas blockade of the stress-induced corticosterone surge with metyrapone pretreatment of pregnant mice abrogated the effect. We conclude that stress-triggered glucocorticoids during pregnancy can increase susceptibility to allergy in offspring. Because inflammation typically includes a stress hormone response, the results also suggest a common pathway by which various injurious exposures during pregnancy might increase offspring susceptibility to asthma.